Formulasi food bars berbahan baku koro pedang putih (Canavalia ensiformis) autoclaving - cooling - Atina Rahmawati; Wirawan (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
White jackbean is type of bean that grows in tropical and subtropical areas. White jackbean has large protein and complex carbohydrate content. The autoclaving - cooling process can be used to change starch into resistant starch in the white jackbe an flour through gelatinization and retrogradation processes. White jackbean flour treated with autoclaving – cooling process can be used as a raw material for the formulation of food bars. Currently food bars have been in great demand along with the needs to consume healthy and nutritious ready-to-eat food. This study aims to determine the appropriate formulation of white jack bean flour treated with autoclaving – cooling process to produce food bars with the best physical, chemical and organoleptic properties.The results showed that the best formulation is the formulation of white jackbean flour : wheat flour = 60 : 40 with 48.81% carbohydrate content, 14.87% protein content, 16.57% fat content, 17.07% moisture content, 2.68% ash content, 2269.3 gf breaking strength, 6.43 N texture, 79.59 color (L), 15.71 color (a), 17.21 color (b), 4.02 color organoleptic, 3.88 flavor organoleptic, 3.83 aroma organoleptic, 3.83 texture organoleptic. and 11,38% resistant starch content.